ChemInform Abstract: Alkaline Earth‐Gold‐Aluminides: Synthesis and Structure of SrAu3Al2, SrAu2.83Al2.17, BaAu2.89Al2.11 and BaAu7.09Al5.91. Issue 10 (February 2016) - Gerke, Birgit; Poettgen, Rainer
Abstract: The title intermetallics are prepared by arc melting of the elements and subsequent annealing (Ta and quartz tubes for Sr and Ba compounds, resp., 825 K, 9 h).